Influence of Magnetic Field Strength on Magnetic Resonance Imaging Radiomics Features in Brain Imaging, an In Vitro and In Vivo Study - Ammari, Samy; Pitre-Champagnat, Stephanie; Dercle, Laurent; Chouzenoux, Emilie; Moalla, Salma; Reuze, Sylvain; Talbot, Hugues; Mokoyoko, Tite; Hadchiti, Joya; Diffetocq, Sebastien; Volk, Andreas; El Haik, Mickeal; et al. (Frontiers in Oncology, 2021)
Objectives: The development and clinical adoption of quantitative imaging biomarkers (radiomics) has established the need for the identification of parameters altering radiomics reproducibility. The aim of this study was to assess the impact of magnetic field strength on magnetic resonance imaging (MRI) radiomics features in clinical practice. Methods: T1 3D SPGR sequence was acquired on 2 phantoms and 10 healthy volunteers on two clinical MR devices from the same manufacturer using two different magnetic fields (1.5T and 3T). Phantoms varied in terms of gadolinium concentrations and textural heterogeneity. 27 regions of interest were segmented (phantom: 21, volunteers: 6) using LIFEX software. 34 features were analyzed. Results: In the phantom dataset, 10 (67%) out of 15 Radiomics features were significantly different when measured at 1.5T or 3T (student’s t-test, p<0.05). Grey level resampling, and pixel size also influence part of texture features. These findings were validated in healthy volunteers. Conclusions: According to daily used protocols for clinical examinations, radiomic features extracted on 1.5T should not be used interchangeably with 3T when evaluating texture features. Such confounding factor should be adjusted when adapting the results of a study to a different platform, or when designing a multicentric trial.